Modelling Rocket System Performance Parameters - Nnorom Achara (Academy Journal of Science and Engineering)
What distinguishes the rocket system from airbreathing engines is that the rocket carries its own propellants, fuel and oxidants.  The modern rocket was originally developed for ballistic missiles.  The operation of the German V2 ballistic missile was not satisfactory because of excessive nose-cone heating,  The Soviet Union launched Sputnik 1 to orbit the earth for 21 days.  The solid and liquid propellants are widely used in rocket propulsion.  Thrust production is necessary in the propulsion of the rocket.  Therefore, the purpose of this study is the development of expression through thrust for the study of the performance characteristics of the rocket.  Mathematical model has been developed and illustrative solutions obtained, plotted and analysed for the relationship between parameters that affect rocket performance.